Active nanocomposite films based on soy proteins-montmorillonite- clove essential oil for the preservation of refrigerated bluefin tuna (Thunnus thynnus) fillets - Echeverría, Ignacio (2018)
This manuscript evaluates the potential application of active nanocomposite films based on soy protein isolate (SPI)-montmorillonite (MMT)-clove essential oil (CEO) to the preservation of muscle fillets of bluefin tuna (Thunnus thynnus) during refrigerated storage, and furthermore analyzes whether the clay diffuses from the package to food. SPI films with: CEO (SPI-CEO), MMT (SPI-MMT), or both CEO and MMT (SPI-MMT-CEO), were prepared and used to cover tuna fillets during 17 days of storage at 2 °C. Polyethylene films were also used as control. Protein films nanoreinforced with 10 g MMT/100 g SPI and activated with CEO were able to decrease microbial growth (evaluated by TVBN and microorganism counts) and lipid autooxidation (evaluated according to the TBA index, FTIR and color parameters) of tuna fillets during the storage period studied. The presence of clay seemed to favor the release of the active principles of clove oil by prolonging its antimicrobial (especially effective to inhibit Pseudomonas spp.) and antioxidant activity over time without observing the diffusion of the clay's own metals (Si and Al) from the nanocomposite materials to the muscle of fish. These results are encouraging for the use of nanocomposite films in food packaging.